2017
DOI: 10.1007/s00431-017-3046-1
|View full text |Cite|
|
Sign up to set email alerts
|

Cost-effectiveness of rule-based immunoprophylaxis against respiratory syncytial virus infections in preterm infants

Abstract: The objective of the paper is to assess the cost-effectiveness of targeted respiratory syncytial virus (RSV) prophylaxis based on a validated prediction rule with 1-year time horizon in moderately preterm infants compared to no prophylaxis. Data on health care consumption were derived from a randomised clinical trial on wheeze reduction following RSV prophylaxis and a large birth cohort study on risk prediction of RSV hospitalisation. We calculated the incremental cost-effectiveness ratio (ICER) of targeted RS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 37 publications
0
17
0
1
Order By: Relevance
“…Blanken et al evaluated the costeffectiveness of targeted prophylaxis (first-year RSVH risk > 10%) in the Netherlands using the MAKI randomized trial, the locally derived validated RISK models for RSVH, Dutch prices, and a 1-year time horizon without discounting. 27 The ICER/QALY for prophylaxis versus nonprophylaxis was €214,748, which was well above the threshold of €80,000 per QALY. The investigators indicated that palivizumab in the late preterm cohort would only be cost-effective if the cost per vial decreased to less than half the current price of €928.…”
mentioning
confidence: 86%
“…Blanken et al evaluated the costeffectiveness of targeted prophylaxis (first-year RSVH risk > 10%) in the Netherlands using the MAKI randomized trial, the locally derived validated RISK models for RSVH, Dutch prices, and a 1-year time horizon without discounting. 27 The ICER/QALY for prophylaxis versus nonprophylaxis was €214,748, which was well above the threshold of €80,000 per QALY. The investigators indicated that palivizumab in the late preterm cohort would only be cost-effective if the cost per vial decreased to less than half the current price of €928.…”
mentioning
confidence: 86%
“…The cost-effectiveness of using the multinational RST has not been formally assessed; however, economic evaluations have been undertaken on the use of other RSTs or risk-factor based approaches to targeting prophylaxis in late preterm 33-35 wGA infants [19,67,68]. The Canadian RST, based on data from the PICNIC study [40], included seven variables: small for GA (<10th percentile); male sex; born early during the RSV season (November, December, January); family history without eczema; subject or siblings in daycare; >5 individuals in the home, including the subject; and, >1 smoker in the household [17].…”
Section: How Effective Is Palivizumab Prophylaxis In Late Preterm Infmentioning
confidence: 99%
“…The AUROC was 0.703 and the cut-off score for low-risk was defined as <16 (3.5% RSVH rate) and for high-risk as ≥16 (10.0% RSVH rate) [41]. Assuming all high-risk infants would receive prophylaxis, a decision model analysis produced an ICER of €214,748 per QALY, for moderately preterm infants 32-35 wGA, which was considered not cost-effective at a threshold of €80,000 per QALY [67]. Another analysis on 33-35 wGA infants, using data from the Spanish FLIP-2 study [39], assessed costeffectiveness based on infants having either 2 major risk factors and 2 minor risk factors (group A), 2 major and 1 minor risk factors (B), or 2 major risk factors (C) [68].…”
Section: How Effective Is Palivizumab Prophylaxis In Late Preterm Infmentioning
confidence: 99%
See 1 more Smart Citation
“…The utility values applied to QALYs calculations were collected from the literature. Baseline utility value for hospitalization was 0.95 (23)(24)(25)(26), whereas a 0.88 utility value was used for PICU, given hospitalization (27,28), 0.59 for hospitalization with acute complications, and 0.5 for PICU with acute complications (29,30). The number of QALYs was calculated as the utility value given to a particular health state multiplied by length of time spent in that state.…”
Section: Utilitiesmentioning
confidence: 99%